Correlation analysis on epidermal growth factor receptor (EGFR) mutations and clinicopathological characteristics in lung adenocarcinomas - Wang, Haitao; Ji, Changhua; Zhou, Chengjun; Li, Hui (Frontiers in Oncology, 2025)
PurposeTo analysis the correlation between EGFR mutations and clinicopathological features in lung adenocarcinomas.Methods139 lung adenocarcinoma cases from the Second Hospital of Shandong University were conducted molecular detection of EGFR mutations. Multiple clinicopathological characteristics were collected and analyzed to identify the relationship with EGFR mutations. The amplification refractory mutation system (ARMS) was performed to detect the EGFR mutations.ResultsDuring the 139 cases, 96 lung adenocarcinoma cases had EGFR mutations. EGFR mutations were associated with smoking history (P=0.0311), tumor size (P=0.0247), tumor subtype (P=0.0003), rhabdomyoid differentiation (P=0.0237) and extracellular mucus (P=0.0013).ConclusionsSmoking history, tumor size, tumor subtype, rhabdomyoid differentiation and extracellular mucus were related to EGFR mutations in lung adenocarcinoma. These histological characteristics might be meaningful to predict EGFR mutations.